Hybrid nanostructures for SERS: materials development and chemical detection - Fateixa, Sara
This review focuses on recent developments in hybrid and nanostructured substrates for SERS (surface-enhanced Raman scattering) studies. Thus substrates composed of at least two distinct types of materials, in which one is a SERS active metal, are considered here aiming at their use as platforms for chemical detection in a variety of contexts. Fundamental aspects related to the SERS effect and plasmonic behaviour of nanometals are briefly introduced. The materials described include polymer nanocomposites containing metal nanoparticles and coupled inorganic nanophases. Chemical approaches to tailor the morphological features of these substrates in order to get high SERS activity are reviewed. Finally, some perspectives for practical applications in the context of chemical detection of analytes using such hybrid platforms are presented.